(untitled) (Research in Agriculture Livestock and Fisheries, 2019)
Monosex Nile tilapia (Oreochromis niloticus) is highly preferred in semi-intensive and intensive culture systems to prevent uncontrolled reproduction and to obtain fast growing male. Production of all male tilapia is being practiced by the hatcheries of Bangladesh mainly by administering androgen hormones (particularly 17-α-methyl-testosterone) with feed in a mixture of undifferentiated fry for about a month. The direct application of hormone to such food chain often arises question in respect to public health and safety. The alternative to this is the production of putative supermales, a rather safe but longer procedure to obtain all male progeny. However, sex determination system in tilapia is fairly complex. Recent developments have resulted in a linkage map and genetic markers that can be used to analyze the sex determination system. For genetic analysis of different genotypes of fish, microsatellite DNA marker ARO120 and ARO121 were used for studying the inheritance pattern for possible sex linkage using Polyacrylamide gel electrophoresis. In case of ARO120, it was observed that the Dam XX was heterozygous; 11 out of 22 female progeny and 10 out of 22 male progeny were found to be heterozygous. In case of ARO121, it was observed that the Dam XX was heterozygous; 16 out of 22 female progeny and 20 out of 22 male progeny were found to be heterozygous. Though the marker polymorphisms were observed in this study, these were excluded from the sexlinkage study due to limited extent of information as sex-linked markers in Nile tilapia BFRI strain. This study provides a baseline for further research using other suitable polymorphic markers for assisting marker-assisted selection. Res. Agric., Livest. Fish.6(1): 143-151, April 2019